Customer Contentment in Outdoor Educational and Training Services - Ahmad Firdaus; Munawan Munawan; Ratna Riandhini (TourEcon: International Journal of Tourism and Economic Studies, 2024)
This research delves into customer satisfaction within the realm of outdoor educational and training services. Through an examination of various factors contributing to client contentment in such settings, this study aims to uncover the dynamics influencing satisfaction levels. By employing qualitative and quantitative methodologies, the research evaluates aspects such as program effectiveness, instructor competence, facility quality, and overall experience satisfaction. The findings offer insights into the significance of meeting customer expectations in outdoor education and training services and provide practical implications for enhancing client contentment in these settings.